Impact of the right ventricular mechanical pattern assessed by three-dimensional echocardiography on adverse outcomes following cardiac surgery - Marius Keller; Alexandra Fábián; Andrea Bandini; Ádám Szijártó; Zoltán Tősér; Béla Merkely; Tim Heller; Marcia-Marleen Dürr; Peter Rosenberger; Attila Kovács; Harry Magunia (Scientific Reports)
Abstract Risk stratification for cardiac surgery is a cornerstone of perioperative management. While the prognostic impact of severe right ventricular (RV) dysfunction is well understood, the added value of the RV mechanical pattern regarding risk prediction remains unknown. We sought to prospectively validate the predictive value of 3D RV mechanics for adverse perioperative outcomes. The clinical and echocardiographic parameters of 439 retrospectively selected patients who underwent various types of cardiac surgery and 3D transesophageal echocardiography were investigated to determine their associations with a composite endpoint of an unfavorable postoperative outcome. Tricuspid regurgitation, 2D RV strains, and 3D measures of left ventricular (LV) and RV function were associated with the composite endpoint. Multivariable logistic regression models revealed that only tricuspid regurgitation, LV ejection fraction and 3D RV global longitudinal strain (GLS) were independently associated with the endpoint. By applying the model to the data of 128 prospectively enrolled patients, only 3D RV GLS remained an independent predictor. A RV GLS cutoff of -17.4% was found to be associated with a 3-fold increased risk for adverse outcomes. This led us to conclude that RV longitudinal deformation derived from 3D echocardiography is predictive of adverse outcomes and should be incorporated in perioperative risk stratification.